Coronary Plaque Regression: A Review of the Role of Lipid-Lowering Agents - Adhikari, Anish; Wutawunashe, Caleb; Kim, Michael; Kodra, Arber (International Journal of Angiology, 2025)
The burden of coronary artery disease (CAD) globally is substantial. Lipid-lowering therapies (LLT) significantly reduce the morbidity and mortality associated with CAD. The advent of more sophisticated imaging modalities of the coronary arteries, including intravascular ultrasound, optical coherence tomography, and coronary computed tomography angiography with calcium scoring, has allowed for evaluation of changes in plaque composition and volume as surrogates of plaque regression. LLTs, particularly statins and proprotein convertase subtilisin/kexin type 9 inhibitors, are effective in reducing low-density lipoprotein cholesterol and reducing cardiovascular mortality. This review synthesizes the evidence on the efficacy of various LLT agents in promoting plaque regression.
Keywords: lipid; plaque regression; IVUS; OCT; statins; cardiovascular disease; cardiovascular risk factors